Paintings in Metropolitan Museum of Art 20240523 - NC (Wikimedia Commons, 2024)
Notice iconographique issue de Wikimedia Commons. Titre: Paintings in Metropolitan Museum of Art 20240523. Paintings in the Metropolitan Museum of Art
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons